Effects of feeds on the particulate organic matter content of water of prawn ponds at two stocking densities - Janeo, Rosy Lumajen (College of Fisheries, University of the Philippines, 1993)
A study was conducted to determine the effects of feeds on the particulate organic matter of prawn ponds at two stocking densities in a Split-Split Plot Design. The stocking densities were : 32,000/ha (Trt.1) and 68,000 (Trt. II). Four 1-ha ponds were used and divided into two sampling points, the downwind (S) and upwind (N) corners while sampling was done before (M1) and after (M2) water exchange. Feeding significantly increased organic matter in the water but did not appreciably increased the organic matter content of the soil. Results obtained on correlation of particulate organic matter with the physic-chemical parameters of the soil and water showed a highly positive correlation with Biochemical Oxygen Demand, NH3-N, NO2-N, phytoplankton density, chlorophyll a and soil organic matter while a highly negative correlation was observed with dissolved oxygen. correlation analysis on particulate organic matter with other physico-chemical parameters like temperature, salinity, pH, phosphate and total nitrogen gave a low and not significant coefficients (P>0.05). Analysis of variance further showed significant differences between management levels but not with treatments and wind directions in almost all of the parameters analyzed.